2018
DOI: 10.1038/s41598-018-26121-0
|View full text |Cite
|
Sign up to set email alerts
|

The Translational and Rotational Dynamics of a Colloid Moving Along the Air-Liquid Interface of a Thin Film

Abstract: This study examines the translation and rotation of a spherical colloid straddling the (upper) air/liquid interface of a thin, planar, liquid film bounded from below by either a solid or a gas/liquid interface. The goal is to obtain numerical solutions for the hydrodynamic flow in order to understand the influence of the film thickness and the lower interface boundary condition. When the colloid translates on a film above a solid, the viscous resistance increases significantly as the film thickness decreases d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…Interfacial self-assembly has been used for the fabrication of colloidal monolayers due to its effectiveness and versatility for the assembly of very diverse materials and has been widely investigated theoretically [1,3,[45][46][47][48][49][50][51][52][53][54][55][56]. In particular, air/water interface self-assembly based on surface confinement and water discharge has been adopted [45].…”
Section: Self-assembly Of Colloidal Monolayersmentioning
confidence: 99%
“…Interfacial self-assembly has been used for the fabrication of colloidal monolayers due to its effectiveness and versatility for the assembly of very diverse materials and has been widely investigated theoretically [1,3,[45][46][47][48][49][50][51][52][53][54][55][56]. In particular, air/water interface self-assembly based on surface confinement and water discharge has been adopted [45].…”
Section: Self-assembly Of Colloidal Monolayersmentioning
confidence: 99%
“…The presence of adsorbed surfactants brings in an additional contribution to the drag, with f d up to ≃ 3, due to the viscous nature of the interface with nonvanishing shear and dilatational viscosities [8,9,15,16,17]. More recent investigations focused on the influence of contact line fluctuations on the drag force [18,19], whereas both the rotational and translational dynamics of a colloid moving at a flat air-liquid interface in a thin film were addressed in [20].…”
Section: Introductionmentioning
confidence: 99%
“…In several experiments it has been observed that the hydrodynamic drag decreases when a larger portion of the particle is immersed in the low viscosity fluid or gas [14][15][16][17][18] . This behavior has been reproduced in theoretical studies, where the drag force is calculated using Stokes hydrodynamics with various boundary conditions, including the presence of shear and dilational surface viscosities 19 , a finite ratio of bulk viscosities 20 , or a solid or membrane boundary on the opposite surface of a thin film 22 .…”
Section: Introductionmentioning
confidence: 76%
“…Colloidal particles are spontaneously adsorbed on to the fluid-fluid interface and energetics govern the state of the system to reach a minimum energy as first observed by Ramsden 12 and Pickering 13 . The dynamics of a spherical particle trapped at an interface between two fluids or fluid and gas is a widely studied problem both experimentally [14][15][16][17][18] and theoretically [19][20][21][22][23][24][25] , due to its importance in various chemical, oil and mineral flotation industries. The hydrodynamic drag of the colloid along the interface depends crucially on the viscosity difference between the two fluids and the particle wetting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation